Priložnostne skladbe v čast cesarju, monarhiji in panslavizmu kot odraz nekaterih staroslovenskih političnih načel in idej po letu 1848 - Cigoj Krstulović, Nataša (Muzikološki zbornik, 2007)
Occasional musical works for the political use with the explicit extra musical purpose - hymns in honour of the Hapsburg monarchy and the emperor Franz Joseph - show a different image and has a different meaning than the prevailing part of the Slovenian music creativity after 1848. In comparison with the patriotic songs with the national-awakening lyrics and songs in folkloric manner they represent only a negligible and trivial part of the Slovenian music creativity. They were the work of the immigrant Czech composers and unimportant music creators whose opinion corresponded with the legitimism of the Slovenian conservative thinking after 1848. These are extreme examples of the functional music. Another example of music in the political use are occasional songs on the politically committed subjects that promoted pan-Slavism and sprang up mostly in the fifties and sixties of the nineteenth century.
Keywords: 19.st.; 19th cent.; glasba; glasbeni nacionalizem; himne; hymns; music; music and politics; music nationalism; occasional music; politics; politika; priložnostna glasba; Slovenia; Slovenija